2020
DOI: 10.1007/s00170-020-06367-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of conventional and additive manufacturing for the production of Ti-6Al-4V knee implant: a life cycle approach

Abstract: This paper explores whether additive manufacturing (AM) is more environmentally friendly than conventional manufacturing (CM) for the production of medical implants. The environmental impact of manufacturing the femoral component of a knee implant made from Ti-6Al-4V material was investigated. One AM method (electron beam melting (EBM)) and one CM method (milling) were analysed for the production of this part. A cradle to grave life cycle approach was utilised for each manufacturing method focusing on the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…2012 ), and anesthetic equipment at two hospitals ( McGain et al. 2017 ); c ) items specific to particular procedures or specialties, such as titanium alloy knee implants ( Lyons et al. 2021 ), custom packs used to deliver newborns ( Campion et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2012 ), and anesthetic equipment at two hospitals ( McGain et al. 2017 ); c ) items specific to particular procedures or specialties, such as titanium alloy knee implants ( Lyons et al. 2021 ), custom packs used to deliver newborns ( Campion et al.…”
Section: Resultsmentioning
confidence: 99%
“…Other functional units employed included: per item (disposable custom packs, Campion et al. 2015 ; knee implants, Lyons et al. 2021 ), per kilogram (medical gloves, Weisz et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work does not only focus on electricity consumption but also on the consumption of fluids and materials. In [20] an environmental study to compare electron beam melting (EBM) and rotation of Ti-6Al-4V pieces was elaborated. [25] performed an LCA of Ti-6Al-4V parts to compare direct additive laser manufacturing (CLAD) and machining.…”
Section: State Of the Artmentioning
confidence: 99%
“…This can be carried out using software like OpenLCA, GaBi, SimaPro. A few research works have been reported using this tool for analyzing the environmental impact of 3D printed parts in the field of polymer filaments, automobile and health sector (DeBoer et al , 2021; Lyons et al , 2021; Ma et al , 2021). But, there were no LCA studies found for 3D printed drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%